1976
DOI: 10.2307/1942394
|View full text |Cite
|
Sign up to set email alerts
|

Forest Overstory Vegetation and Environment on the Missouri River Floodplain in North Dakota

Abstract: The study area, bounded north and south by two large reservoirs, includes the most extensive remnant of floodplain forest in the Dakotas. Structure and composition of the forest overstory are strongly related to stand age and horizontal and vertical position on the floodplain. Populus deltoides Marsh. and Salix amygdaloides Anders. predominate in young stands which generally occur on low terraces near the center of the floodplain. Fraxinus pennsylvanica var. lanceolata (Borkh.) Sarg., Acer negundo L., Ulmus am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
269
2
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(286 citation statements)
references
References 42 publications
6
269
2
3
Order By: Relevance
“…The source of the abundant LWD in the river was an extensive floodplain forest, of which only isolated stands remain (Johnson et al, 1976). Human activity on the Missouri River has greatly altered LWD abundance and dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The source of the abundant LWD in the river was an extensive floodplain forest, of which only isolated stands remain (Johnson et al, 1976). Human activity on the Missouri River has greatly altered LWD abundance and dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Attenuation of peak flows since Garrison Dam was completed in 1953 (Figures 1, 2a) has greatly reduced channel migration (Johnson, 1992;Shields et al, 2000) and virtually eliminated overbank flows. Before flow regulation, spring and summer floods caused lateral bank erosion and channel avulsions that caused trees (mostly cottonwoods, Populus deltoides Marsh; Johnson et al, 1976) to fall into the channel at outside bends (Chittenden, 1962). At the same time, new stands of cottonwood and willow (Salix spp.)…”
Section: Introductionmentioning
confidence: 99%
“…Decades of observation of the effects of human alteration of natural flow regimes have provided explanations of why altering hydrologic variability in rivers is ecologically harmful (e.g. Johnson et al, 1976;Tyus, 1990;Arthington et al, 1991;Hill et al, 1991;Sparks, 1995;Toth, 1995;Castleberry et al, 1996;Stanford et al, 1996;Richter et al, 1997). Other studies have shown the harmful effects of altering flow by constraining rivers with artificial levees, dikes or groynes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…CARBIENER 1970CARBIENER , 1984JOHNSON et al 1976;KLINGE et al 1983;KLIMO 1985;TRÈMOLIÉRES et al 1998). Examples of negative effects such as decrease of biomass, lower landscape diversity were developed in studies in the Missouri and other river floodplains (JOHNSON et al 1976;LUGO et al 1990). Dams and channel diversions considerably alter environmental conditions for riparian and aquatic organisms (ALLAN, FLECKER 1993;DYNESIUS, NILSSON 1994) and greatly modify fluvial dynamics (GALAY 1983), the natural regime of disturbance (e.g.…”
mentioning
confidence: 99%
“…The literature is unanimous on the relationship between hydrology (flooding duration and frequency, annual ground water level fluctuations) and ecosystem functioning (ground water chemistry, bio-geochemical cycle, productivity, species richness and diversity) (e.g. CARBIENER 1970CARBIENER , 1984JOHNSON et al 1976;KLINGE et al 1983;KLIMO 1985;TRÈMOLIÉRES et al 1998). Examples of negative effects such as decrease of biomass, lower landscape diversity were developed in studies in the Missouri and other river floodplains (JOHNSON et al 1976;LUGO et al 1990).…”
mentioning
confidence: 99%